Application of Induced Polarization and Resistivity to the Determination of the Location of Minerals in Extrusive Rock Area, Southern Mountains of Java, Indonesia - Moh Saparun; Rajabal Akbar; Mahmuddin Marbun; Aparna Dixit; Arti Saxena (CV FOUNDAE, 2022)
Mountainous areas often have a lot of natural wealth. The existence of geological appearances in the form of outcrops which are products of intrusion and alteration, indicates that the Pacitan area is a mineralized zone. In this study, geophysical measurements were carried out using the Induced Polarization (IP) method in the area where mineralization was suspected. The polarization induction method is expected to prove the presence of a mineralized zone in the Pacitan area. From the research results, line 1, line 4, line 5, line 6 and line 7 are areas with high chargeability values. So it can be proven that the area with high resistivity and high chargeability is an area with mineralization. Judging from the geological conditions on the surface, there are also outcrops which show that there is an intrusion and the result of alteration. So it can be concluded that the area has a fairly high mineralization. In measuring the correlation between magnetic anomalies and IP, the results are very supportive of each other that the area is a mineralized area, if we look at the resistivity, and chargebility.